First ever probable oats (Avena sativa) QTLs mapped on chromosome 1 and 7 for pyrenophora leaf spot resistance in India - HILLI, HARSHAVARDAN J; KAPOOR, RAHUL; SRIVASTAV, PUJA; SHARMA, PRITI (The Indian Journal of Agricultural Sciences, 2024)
An experiment was conducted during 2021–22 at Punjab Agricultural University, Ludhiana, Punjab for the development of linkage map and identification of QTLs for pyrenophora or Helminthosporium leaf spot resistance in oats (Avena sativa L.). A total of 96 F2 plants were used which was derived from the cross EC/0007662 (resistant source) and EC/0131291 (susceptible source). Linkage map was constructed for genotypic data of 96 population lines with 24 polymorphic SSR markers using QTL cartographer. A total of 7 linkage groups (LGs) had been generated from this data. But out of 7 LGs, 5 LGs remained individually at 0 position (unlinked) i.e. belonged to different group each and LG1 and LG7 were grouped. First LG included ABAM232, ABAM493 and ABAM077 from 0 to 66.5 cM. Similarly, 7th LG had two marker position i.e. ABAM342 and ABAM425. Maximum distance between the two markers was found to be 33.4 cM (between the marker interval of ABAM232 and ABAM497. Further QTL analysis was done using cartographer with composite interval mapping to identify the QTLs associated with disease resistance by comparing the phenotypic data of F2 population for disease and genotypic data of the population. The work reported here constitutes a major step toward identification of genetic regions responsible for disease resistance. However, the utility of QTL for marker assisted selection requires that QTLs are localized in a narrow region tightly linked with associated markers. The result of the experiment can be used for marker assisted breeding to transfer such genes identified as part of our research in order to reduce disease severity and yield losses in oats.